DIPLOMASI DAN PATRIOTISME SULTAN SYARIF KASIM II: KAJIAN LITERATUR TERHADAP KONTRIBUSI EKONOMI DAN POLITIK BAGI KEMERDEKAAN REPUBLIK INDONESIA - Rahmat Putra An-Nur; Bunari Bunari; Nurdiansyah Nurdiansyah (Nusantara Hasana Journal, 2026)
At the beginning of Indonesian independence, Sultan Syarif Kasim II donated all the wealth and territory of the Siak Kingdom to the newly established Republic of Indonesia. This research aims to: (1) analyze the form of political diplomacy of Sultan Syarif Kasim II in supporting the sovereignty of the Republic of Indonesia; (2) identify the economic contribution of Sultan Syarif Kasim II to the sustainability of the initial capital of the Republic of Indonesia government; and (3) evaluate the long-term impact of Sultan Syarif Kasim II's political and economic choices on strengthening Indonesia's position in the early days of independence. This research uses a historical research type with a literature study approach. (1) Sultan Syarif Kasim II's political diplomacy was realized through five main forms, namely political loyalty diplomacy, symbolic, inter-elite, and political survival; (2) the Sultan's economic contribution included the transfer of funds worth 13 million guilders along with the territory of the Siak Kingdom and its contents; and (3) the long-term impacts of this decision include strengthening the legitimacy of the Republic of Indonesia, forming the foundations of the local economy, and maintaining the Malay cultural heritage and historical identity of the Siak Sri Indrapura Sultanate to the present day.